Sociology of crime, law and deviance. Vol. 2 - Ulmer, Jeffery T., 1966- (JAI Press, 2000. Elsevier : Architectural Press, 2000)
"Sociology of Crime, Law and Deviance" is an annual series of volumes that publishes scholarly work in criminology and criminal justice studies, sociology of law, and the sociology of deviance and social control. These are very broad topics, and the series reflects this breadth. The series includes theoretical contributions, critical reviews of literature, empirical research, and methodological innovations. The series especially showcases "big picture" pieces that review and critically reconceptualize what is known and what remains to be understood about broad directions of research and theorizing about crime, justice, law, deviance, and social control. In addition, the series showcases a diversity of methodological approaches. "Volume 2" demonstrates such methodological diversity by presenting quantitative studies, ethnographies and discourse analyses. Through an application of these methodologies, the authors examine sanctions, crime and fear and legal and social control organizations and processes. The volume concludes with four chapters contributing to theory development.